Differentially expressed seed aging responsive heat shock protein OsHSP18.2 implicates in seed vigor, longevity and improves germination and seedling establishment under abiotic stress - Kaur, Harmeet; Petla, Bhanu P.; Kamble, Nitin U.; Singh, Ajeet; Rao, Venkateswara; Salvi, Prafull; Ghosh, Shraboni; Majee, Manoj (Frontiers in Plant Science, 2015)
Small heat shock proteins (sHSP) are a diverse group of proteins and are highly abundant in plant species. Although majority of these sHSPs were shown to express specifically in seed, their potential function in seed physiology remains to be fully explored. Our proteomic analysis revealed that OsHSP18.2, a class II cytosolic HSP is an aging responsive protein as its abundance significantly increased after artificial aging in rice seeds. OsHSP18.2 transcript was found to markedly increase at the late maturation stage being highly abundant in dry seeds and sharply decreased after germination. Our biochemical study clearly demonstrated that OsHSP18.2 forms homooligomeric complex and is dodecameric in nature and functions as a molecular chaperon. OsHSP18.2 displayed chaperone activity as it was effective in preventing thermal inactivation of Citrate Synthase. Further, to analyze the function of this protein in seed physiology, seed specific Arabidopsis overexpression lines for OsHSP18.2 were generated. Our subsequent functional analysis clearly demonstrated that OsHSP18.2 has ability to improve seed vigor and longevity by reducing deleterious ROS accumulation in seeds. In addition, transformed Arabidopsis seeds displayed better performance in germination and cotyledon emergence under adverse conditions as well. Collectively, our work demonstrates that OsHSP18.2 is an aging responsive protein which functions as a molecular chaperon and possibly protect and stabilize the cellular proteins from irreversible damage particularly during maturation drying, desiccation and aging in seeds by restricting ROS accumulation and thereby improves seed vigor, longevity and seedling establishment.